Seeking a purer Christian life : sayings and stories of the Desert Fathers and Mothers - Beasley-Topliffe, Keith (Nashville, Tenn. : Upper Room Books, 2000)
Een handleiding om een mooi christelijk leven te lijden.
Keywords: Desert Fathers -- Quotations; Spiritual life -- Christianity -- Quotations, maxims, etc